PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS PADA SEKTOR PERUSAHAAN JASA INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI DI BURSA EFEK INDONESIA PERIODE - Damayanti, Novita Dwi; Kusumaningtias, Rohmawati (Jurnal Akuntansi AKUNESA, 2020)
This study aims to provide empirical evidence related to the effect of corporate governance mechanisms on financial distress in 2015-2017. The research sample consisted of 129 infrastructure, utilities and transportation companies. The data analysis technique used in this study is multiple regression analysis. Hypothesis test results indicate that the independent director and audit committee have a positive effect on financial distress. Meanwhile, institutional ownership, managerial ownership and independent commissioners have no effect on financial distress.